A New Candidate Missense Mutation (Leu 1657 Ile) in an Apparently Asymptomatic Type 2A (Phenotype IIA) von Willebrand Disease Family - Enayat, M. S.; Guilliatt, A. M.; Surdhar, G. K.; Theophilus, B. D. M.; Hill, F. G. H. (Thrombosis and Haemostasis, 2000)
Type 2A von Willebrand disease (VWD) is mostly an autosomal dominantly inherited bleeding disorder characterised by a qualitative defect of von Willebrand factor (VWF). Mutation screening was used to screen the whole of VWF gene followed by direct sequencing to detect the mutation in a father and son diagnosed with type 2A (phenotype IIA) von Willebrand disease. A C5219 to A transversion was detected predicting Leucine to Isoleucine substitution in codon 1657. This novel missense mutation which was also identified by MboI restriction enzyme analysis, was found in both patient and his father but not in any other unaffected family member or 50 unrelated normal individuals. This substitution was reproduced by in vitro site directed mutagenesis of full-length VWF cDNA and transiently expressed in COS-7 cells. The corresponding recombinant VWF protein exhibited the full spectrum of VWF multimers, suggesting that the abnormal multimer seen in the patient results from increased proteolysis.
Keywords: Type 2A VWD; mutation detection; chemical cleavage mismatch detection; recombinant VWF